(3ESJQGJjLjI eMGQHI GdaSGO GdGOGQj hGdeGdj (B:s (3eONd JcGedj (B/s - (3WGdH, YdGA aQMGfs; (3GdYGeQj, Ydj MSjf MejOj s ((3YeGf(B: s (3OGQ GdGjGe(B, s, 2015)
(3jVe eaghe GdaSGO GdEOGQj, GdYhGed GdeSGYOI Ydi GdaSGO GdEOGQj, GSJQGJjLjI MSf GNJjGQ GdbjGOI GdGOGQjI , eOGNd hfXQjGJ GdbjGOI, GSJQGJjLjI HfGA GdbjGOI GdGSJQGJjLjI, GSJQGJjLjI GYJeGO GdTaGajI hGdGaUGM aj GdYed GdGOQj, GdeUWdMGJ GdeQJHWI HGdTaGajI , SJQGJjLjGJ ecGaMI GdaSGO GdGOGQj GdGNQi , efXeGJ YGdejI aj eLGd eMGQHI GdaSGO GdGOGQj hGdeGdj hJLGQH YGdejI(B.s
Keywords: (3GdEOGQI, GdaSGOs; (3GdEUdGM GdEOGQjs; (3GdaSGO GdEOGQjs